Global genetic diversity of Infectious Salmon Anemia Virus (ISAV) a scoping review protocol - Persia Carol Thapa; Ahsan Raquib; Kim Mears; Javier Sanchez; Sonja Saksida; Keith Larry Hammell; Krishna Kumar Thakur (PLoS ONE, 2025)
Background Infectious salmon anemia virus is one of the most important pathogens responsible for causing infectious salmon anemia in Atlantic salmon (Salmo salar). Following its first emergence in 1980s in Norway, it has been reported in several salmon producing countries worldwide, with new variants frequently reported. These variants mostly exhibit differences in segments 5 and 6 of the genome, which contribute to the genetic diversity and variability in virulence. Despite the considerable economic losses associated with ISA, there remains a critical gap in available information on genetic diversity and classification. This study aims to provide a comprehensive and up-to-date synopsis of all known ISAV variants worldwide. Methods The Population, Concept, Context approach was used to formulate the research primary question. The primary research question of this review is “What variants of ISAV with respect to segment 5 and 6 has been identified globally in Atlantic salmon?” To address this question, four databases: PubMed, CAB Abstracts via (EBSCO host), Scopus, and the Earth, Atmospheric & Aquatic Science Collection via ProQuest will be used for primary literature search with no language and geographical area restrictions. Studies will be screened using predefined inclusion and exclusion criteria and will be imported in COVIDENCE. Two co-authors will independently screen, extract data, and assess the selected studies. Any discrepancies between the authors will be resolved with the assistance of two other co-authors in each stage of the protocol. Discussion To the best of our knowledge, this protocol outlines the first scoping review which will provide insights into the genetic diversity of ISAV, offering a comprehensive overview of the reported variants and their distribution globally. These findings could enhance our understanding of the genetic diversity of the virus, help customize mitigation strategies based on variants involved and provide foundation to develop a universally accepted nomenclature system.